Early Suppression of Macrophage Gene Expression by Leishmania braziliensis - Sousa, Rosana; Andrade, Viviane M.; Bair, Thomas; Ettinger, Nicholas A.; Guimarães, Luana; Andrade, Laura; Guimarães, Luiz H.; Machado, Paulo R. L.; Carvalho, Edgar M.; Wilson, Mary E.; Schriefer, Albert (Frontiers in Microbiology, 2018)
Leishmania braziliensis is an intracellular parasite that resides mostly in macrophages. Both the parasite genome and the clinical disease manifestations show considerable polymorphism. Clinical syndromes caused by L. braziliensis include localized cutaneous (CL), mucosal (ML) and disseminated leishmaniasis (DL). Our prior studies showed that genetically distinct L. braziliensis clades associate with different clinical types. Herein we hypothesized that: (1) L. braziliensis induces changes in macrophage gene expression that facilitates infection; (2) infection of macrophages with strains associated with CL (clade B), ML (clade C) or DL (clade A) will differentially affect host cell gene expression, reflecting their different pathogenic mechanisms; and (3) differences between the strains will be reflected by differences in macrophage gene expression after initial exposure to the parasite. Human monocyte derived macrophages (MDMs) were infected with L. braziliensis isolates from clades A, B, or C. Patterns of gene expression were compared using Affymetrix DNA microarrays. Many transcripts were significantly decreased by infection with all isolates. The most dramatically decreased transcripts encoded proteins involved in signaling pathways, apoptosis or mitochondrial oxidative phosphorylation. Some transcripts encoding stress response proteins were up-regulated. Differences between L. braziliensis clades were observed in the magnitude of change, rather than the identity of transcripts. Isolates from subjects with metastatic disease (ML, DL) induced a greater magnitude of change than isolates from CL. We conclude that L. braziliensis enhances its intracellular survival by inhibiting macrophage pathways leading to microbicidal activity. Parasite strains destined for dissemination may exert a more profound suppression than less invasive L. braziliensis strains that remain near the cutaneous site of inoculation.